Justice and ethics: towards a new platform for tourism and sustainability. Issue 2 (4th March 2021) - Jamal, Tazim; Higham, James
Abstract: In times of upheaval and uncertainty justice has come to the fore as a key principle to guide tourism development and policy. Justice is being sought by individuals, groups and societies, as vulnerable individuals and populations seek to be able to protect themselves from longstanding and deeply embedded historical, and new emerging forms of, injustice. In response, this special issue presents a range of theoretical perspectives and empirical insights into justice and tourism. Given the early stage of theory building in this field, tourism researchers are well served by exploring the multi-/inter-/trans-disciplinary knowledge domains in which theories of justice are being addressed. In this paper frame some emerging principles and approaches to justice and tourism as addressed in the special issue, including social justice, equity and rights; inclusiveness and recognition; sustainability and conservation; well-being, belonging and capabilities; posthumanistic justice; and governance and participation. In doing so we outline the wide range of issues and insights for 'just' tourism that demand urgent and rigorous scholarly attention. A nascent new platform of research on justice and ethics is emerging to guide tourism and sustainability. This special issue offers valuable insights and guidance towards this timely and important research agenda.